Therapeutic collaboration and the assimilation of problematic experiences in emotion-focused therapy for depression: Comparison of two cases. (1st November 2016) - Ribeiro, Eugénia; Cunha, Carla; Teixeira, Ana Sofia; Stiles, William B.; Pires, Nuno; Santos, Beatriz; Basto, Isabel; Salgado, João
Abstract: Objective: The Assimilation model argues that therapists should work responsively within the client's therapeutic zone of proximal development (TZPD). This study analyzed the association between the collaborative processes assessed by the Therapeutic Collaboration Coding System (TCCS) and advances in assimilation, as assessed by the Assimilation of Problematic Experiences Scale (APES).Method: Sessions 1, 4, 8, 12, and 16 of two contrasting cases, Julia and Afonso (pseudonyms), drawn from a clinical trial of 16-sessions emotion-focused therapy (EFT) for depression, were coded according to the APES and the TCCS. Julia met criteria for reliable and clinically significant improvement, whereas Afonso did not.Results: As expected, Julia advanced farther along the APES than did Afonso. Both therapists worked mainly within their client's TZPD. However, Julia's therapist used a balance of supporting and challenging interventions, whereas Afonso's therapist used mainly supporting interventions. Setbacks were common in both cases.Conclusions: This study supports the theoretical expectation that EFT therapists work mainly within their client's TZPD. Therapeutic exchanges involving challenging interventions may foster client change if they occur in an overall climate of safety.